2023
DOI: 10.20944/preprints202302.0101.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modeling of Soil Water Erosion in Tunisia Using Geospatial Data and Integrated Approach of RUSLE and GIS

Abstract: Soil erosion is one of the most important environmental problems which can have various negative consequences, such as land degradation affecting the sustainable development and the agricultural production, especially for developing countries like Tunisia. Moreover, soil erosion is a major problem around the world because of its effects on soil fertility by nutriment loss and siltation in water bodies. Apart from this, soil erosion by water is the most serious type of land loss in several regions both locally … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 46 publications
1
0
0
Order By: Relevance
“…However, other research results showed that the distribution profiles of heavy metals in roadside soils were not always significantly correlated with road distance (Zhang et al, 2012). Referring to the standards reported by Serbaji (2000) Pb (18 mg/kg), Zn (39 mg/kg), Cr (41 mg/kg), Cu (13 mg/kg), we noted that the Zn contents exceeding the threshold have reached a distance of 50m near Gremda road, 10m near Tunis and Manzel Chaker roads. For Pb, the contamination has reached the same distance as Zn for Gremda and Tunis roads while for Manzel Chaker road, the contamination did not exceed three meter in the vicinity of the road.…”
Section: Soil Contaminationsupporting
confidence: 55%
“…However, other research results showed that the distribution profiles of heavy metals in roadside soils were not always significantly correlated with road distance (Zhang et al, 2012). Referring to the standards reported by Serbaji (2000) Pb (18 mg/kg), Zn (39 mg/kg), Cr (41 mg/kg), Cu (13 mg/kg), we noted that the Zn contents exceeding the threshold have reached a distance of 50m near Gremda road, 10m near Tunis and Manzel Chaker roads. For Pb, the contamination has reached the same distance as Zn for Gremda and Tunis roads while for Manzel Chaker road, the contamination did not exceed three meter in the vicinity of the road.…”
Section: Soil Contaminationsupporting
confidence: 55%